ANALISIS YURIDIS DIREKSI PERSEROAN TERBATAS YANG TIDAK MENYELENGGARAKAN RAPAT UMUM PEMEGANG SAHAM TAHUNAN BERDASARKAN PASAL 79 AYAT (1) UNDANG- UNDANG REPUBLIK INDONESIA NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Yasin Yasin; Arrisman (JOURNAL OF LAW AND NATION, 2023)
This research aims to conduct a juridical analysis of the Directors of Limited Liability Companies (PT) which do not hold Annual General Meetings of Shareholders (AGMS) in accordance with the provisions of Article 79 Paragraph (1) of Law of the Republic of Indonesia Number 40 of 2007 concerning Limited Liability Companies. This research uses normative legal research methods with a statutory approach and a conceptual approach. The results of the analysis show that failure to hold an AGMS by PT Directors can have serious legal consequences, including potential legal violations and negative impacts on the interests of shareholders. The existence of the AGMS as a shareholder control mechanism is strictly regulated in law to ensure transparency, accountability and shareholder participation in company strategic decision making. In this context, this research also identifies factors that cause the PT Board of Directors to not hold an AGMS, such as a lack of understanding of legal regulations, unsupportive internal policies, or even negligence of related parties. Therefore, efforts are needed to improve and strengthen regulations and legal awareness among business actors so that the implementation of the AGMS can be carried out effectively in accordance with the spirit of the law. In conclusion, the failure to hold an AGMS by PT Directors is a serious problem that requires legal attention and system improvements. This research contributes to understanding the impact of law and its causal factors, and emphasizes the importance of compliance with legal regulations to maintain company integrity and sustainability.